Serbia and Montenegro : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2004)
This paper focuses on Serbia and Montenegro's Poverty Reduction Strategy Paper (PRSP). Through the process of developing the Poverty Reduction Strategy, national indicators in line with the Millennium Development Goals have been identified. The poverty reduction strategy for the Union focuses on establishing conditions for dynamic and equitable economic growth, through the creation of a stable macroeconomic environment and favorable investment climate to create employment, reduce economic vulnerability, and establish key programs to directly promote employment among the poor.